Analisis Finansial Penambangan Runtuhan Level Ekstraksi Tambang Bawah Tanah PT XYZ - Wayangkau, Edoardo Stevie; Zulbainarni, Nimmi; Hartoyo (School of Business, Bogor Agricultural University (SB-IPB), 2022)
This study aims to conduct a financial analysis on extraction level mining at PT XYZ's DOZ underground mine. The cave of the extraction level in question is the pillars of panels 22 to panel 27. The age of this project is about 2.4 years which has started in July 2019 and is expected to end in December 2021. Actual production in 2020 if added with projections in 2021 will be able to obtain production of 323,044 tons with an average content of 1.58% Cu and 0.80ppm Au where the average price of Cu is USD 3.3/lb and Au is USD 1,786/oz, the predicted total revenue will be USD 36,125.622. After deducting capital costs, operational costs, taxes and royalties, the net income of this mining business is around USD 19,771,933. Obtaining this advantage when using a discount rate of 8%, it can be seen that NPV is at USD 16,925,310 (>1), BCR is at 1.10 (>1) and IRR is 218% (>1). Information will describe that this project will bring profit. The sensitivity test carried out on four parameters commodity prices, capital costs, operational costs and interest that commodity prices are very sensitive to any increase or decrease in price per unit. Keywords: analysis financial, underground mine, cash flow, discounted cash flow, sensitivity analysis.